ANALISIS KORELASI PREDIKSI PERUBAHAN GENANGAN ROB TERHADAP PREDIKSI PERUBAHAN ZONA NILAI TANAH DI KECAMATAN SEMARANG UTARA - Ikhsan, Edi; Suprayogi, Andri; ., Hani'ah (Jurnal Geodesi UNDIP, 2012)
In the coastal region geomorphology process on going of a complex so that the is a dynamic system. Physical processes and human intervention to separate the pressure on coastal areas. Semarang coastal area including northern Semarang district has a sloping topography with a slope of 0-2%. With a sloping topography, the city of Semarang is very vulnerable to the impact caused by rising sea levels. One thing that often happens is that the flood tide (rob). If sea levels continue to rise, it can result in increasing the extent of inundation rob a place in the city of Semarang. So it can be assumed that the pool would rob correlated to the value of the land. This study used the mean sea  level data years 1985-2010 of  the final project Catur Julianto  in 2011, data reduction in the face of the land in Semarang, data from the spot height semarang topographic maps, data NJOP per meter of land in the district north Semarang years 1994-2011, and map of the zone  land value  in 2011.  This research will  rob  prediction  maps  generated  in 2015,  2020,  and 2025  in Semarang on Safe inundation scenarios, HHWL, MSL, and LLWL, rob our predictions in districts north Semarang  zone  land value,  the price of land according  to  land value zone code 2015, 2020, and 2025, and the correlation of changes rob a pool of predictions to changes in the soil zone. The results showed that the pool of rob in the city of Semarang each year will increase. The main cause is the decline in the face of earth is happening in the city of Semarang. While the value of land in areas prone to  rob  it  tends to go up  from  year  to year.  2015,  2020,  and 2025  is predicted to  be at  a maximum  price  of  AU  in the  village  code Dadapasari  and minimum  prices  are on  the  AW  code  Lor village  stage. While the  correlation of  changes in  the scenario  inundation  zone  rob  to changes in  the value of land in an area safe from inundation rob predicted by 94%, were flooded when HHWL by 82%, and were inundated when the MSL by 73%.